A survey on hydration and use of plastic water bottles among Italian health sector workers - Lugli, Camilla; Palandri, Lucia; Pedretti, Simona; Bacchi, Romana; Altariva, Daniela; Guerzoni, Giulia; Sala, Alessia; Vaccari, Claudia; Filippini, Tommaso; Righi, Elena; Vinceti, Marco; Romani, Gabriele (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Modena’s Local Health Authority (AUSL) is a public service with more than 5,000 employees. In its facilities, drinking water is available as tap water. However, disposable plastic bottles are also widely used, thus increasing plastic waste. Study design and methods. In the present study, we aimed to investigate employees’ drinking habits through an ad hoc 10-item online questionnaire, which was administered in spring 2023. Results. Of the 584 participants (10.8% response rate), 75% of workers reported drinking less than 1.5 liters of water per day. In addition, 74% of workers brought water from home, while 62% used disposable plastic containers bought in the workplace or outside. When asked if they would appreciate a water refilling station in the workplace, whether that would induce them to consume less plastic and to drink more water, 91%, 82%, and 72% of workers said “yes”, respectively. By installing water coolers, the estimated mean number of plastic bottles spared every day at the AUSL would be about 6,000. Conclusions. Our data shed light on most employees’ perceived need for alternative sources of drinking water, not only in order to drink more for health benefits, but also to reduce plastic usage in favor of reusable, more environmentally friendly materials